The Role of Ease of Use, Security, Benefit, and Discounts on the Decision to Use ShopeePay by the Younger Generation - Tibo, Octavianus; Ngion, Rilly Injilya; Indrajit, Indrajit (PT FORMOSA CENDEKIA GLOBAL, 2025)
The development of digital technology has encouraged the increasing use of digital wallets, including ShopeePay, which is widely used by Generation Z. This study aims to analyze the role of ease of use, security, utility, and discounts on Generation Z's decision in using ShopeePay. The research uses a correlational quantitative method with the PLS-SEM approach. Data was collected through a questionnaire with a purposive sampling technique, and obtained 199 respondents who had used ShopeePay more than once. The results of the study show that security, usefulness, and discounts have a positive and significant effect on the decision to use ShopeePay, while ease of use does not have a significant effect. These findings confirm that Generation Z is more concerned about benefits, security, and discount benefits than the convenience that has become the basic standard of digital applications.